Sentiment and economicactivity in Brazil (REGE Revista de Gestão, 2024)
Purpose: Analyze how sentiment affects economic activity in Brazil.Design/methodology/approach: Based on a nonlinear autoregressive distributed lag (NARDL) model, we examine in detail the short-term and long-term asymmetric impacts between the variables during the period from January 2007 to December 2020.Findings: There are three main results of this study. First, sentiment is an important factor for economic activity in Brazil, and its effect possibly occurs through the channels of consumption and investment, which are the two main components of economic growth. Second, sentiment affects economic activity in different ways in the short and the long term: in Brazil although in the short-term immediate shocks of sentiment may be confusing, the negative shocks from previous periods have a negative impact on economic activity. Third, the effect of shocks of optimism and pessimism on economic activity is asymmetric, and in the long run only shocks of optimism have a significant and positive impact.Originality: The relationship between sentiment and economic activity is still a controversial issue in the literature and this study seeks to advance its understanding in Brazil.